Analysis of transcriptome and metabolome characteristics of blood in yaks at different reproductive stages - Kang, Yandong; Pei, Jie; Xiong, Lin; Kong, Xiangying; Liu, Fujun; Zhou, Yuqing; Shang, Shengbin; Feng, Yulong; Li, Haiqin; Wu, Xiaolei; Chu, Min; Zhao, Shoubao; et al. (Frontiers in Veterinary Science, 2025)
The reproductive physiology of yaks differs significantly from that of other cattle breeds due to late sexual maturity, low fecundity and short estrus time. How to improve the reproductive efficiency of yaks has become the main research content and goal of yak reproduction technology. In this study, we collected blood samples from adult female yaks (4–8 years old) during different reproductive periods, including the period of anestrus (Y-A), estrus (Y-E) and pregnancy (Y-P), and investigated the changes of RNA expression and steroid hormone levels in yaks during different reproductive periods by using RNA-seq and target metabolomics, and screened for the genes and regulatory pathways. DEGs such as PDK4, ALAS2, GLP1R, SLC25A39, PGAP6, FOS, CD36, MMP9 and BCL-6 were identified to play key roles in ovarian function, follicular development, hormone homeostasis and energy metabolism. Functional annotation and enrichment analysis indicated that DEGs were involved in ovarian angiogenesis, hormone synthesis and follicular development. In order to reveal the deep interaction between steroid hormone metabolism and gene expression, the weighted gene co-expression network analysis (WGCNA) method was used. It was found that SLC25A39 may affect glucocorticoid homeostasis and physiological readiness by regulating energy metabolism during anestrus, MARCHF2 and DHEA may be closely related to reproductive hormone fluctuation and system activation during estrus, glucocorticoid down-regulation in pregnancy and maintenance of hormone homeostasis and regulation of immune tolerance by DHEA. The results of this study provide a theoretical basis for improving the reproductive performance of yaks and further analysing the reproductive characteristics of yaks.